Targeting DNA damage response as a potential therapeutic strategy for head and neck squamous cell carcinoma - Lei, Huimin; He, Ading; Jiang, Yingying; Ruan, Min; Han, Nannan (Frontiers in Oncology, 2022)
Cells experience both endogenous and exogenous DNA damage daily. To maintain genome integrity and suppress tumorigenesis, individuals have evolutionarily acquired a series of repair functions, termed DNA damage response (DDR), to repair DNA damage and ensure the accurate transmission of genetic information. Defects in DNA damage repair pathways may lead to various diseases, including tumors. Accumulating evidence suggests that alterations in DDR-related genes, such as somatic or germline mutations, single nucleotide polymorphisms (SNPs), and promoter methylation, are closely related to the occurrence, development, and treatment of head and neck squamous cell carcinoma (HNSCC). Despite recent advances in surgery combined with radiotherapy, chemotherapy, or immunotherapy, there has been no substantial improvement in the survival rate of patients with HNSCC. Therefore, targeting DNA repair pathways may be a promising treatment for HNSCC. In this review, we summarized the sources of DNA damage and DNA damage repair pathways. Further, the role of DNA damage repair pathways in the development of HNSCC and the application of small molecule inhibitors targeting these pathways in the treatment of HNSCC were focused.